Benefits and Limitations of Computer Gesture Therapy for the Rehabilitation of Severe Aphasia - Roper, Abi; Marshall, Jane; Wilson, Stephanie (Frontiers in Human Neuroscience, 2016)
Aphasia intervention has made increasing use of technology in recent years. The evidence base, which is largely limited to the investigation of spoken language outcomes, indicates positive treatment effects for people with mild to moderate levels of aphasia. Outcomes for those with severe aphasia, however, are less well documented and – where reported – present less consistent gains for measures of spoken output. This study investigates the effects of a purpose-built gesture therapy technology for people with severe aphasia: GeST+. Study outcomes show significant improvement in gesture production abilities for adults with severe aphasia following computer intervention. They indicate no transfer of effects into naming gains or interactive gesture. Outcomes offer encouraging results for computer therapy methods within this hitherto under-researched population but indicate a need for further refinement of interventions in order to maximize persistence of effects and generalization into everyday communication.